Ambiente de ensino de redes de computadores baseado em nuvem - SANTOS, Bruno Serejo dos (2017)
When teaching computer networks, the assembly of physical laboratories for related courses can be prohibitively expensive, in addition to requiring a constant updating of the hardware. Softwares such as Netkit allow the creation of virtual network laboratories using only one computer, however they need a configuration stage that can be complex and still require individual physical machines per student. This paper proposes a cloud environment for computer networks teaching, which allows Netkit to run on virtual machines preconfigured in the Amazon AWS cloud. In addition, a web portal is available with several scripts ready to be instantiated in the cloud and used from anywhere.